2020
DOI: 10.1098/rsif.2019.0689
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the behavioural variability of confined cell migration

Abstract: Cell-to-cell variability is inherent to numerous biological processes, including cell migration. Quantifying and characterizing the variability of migrating cells is challenging, as it requires monitoring many cells for long time windows under identical conditions. Here, we observe the migration of single human breast cancer cells (MDA-MB-231) in confining two-state micropatterns. To describe the stochastic dynamics of this confined migration, we employ a dynamical systems approach. We identify statist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 85 publications
0
28
0
Order By: Relevance
“…Contact Acceleration Maps Reveal Dynamics of Cell-Cell Interactions Here, we aim to describe the underlying interaction dynamics that capture the full stochastic long-timescale behavior of repeatedly colliding cell pairs. The dynamics of single migrating cells are well described by an equation of motion that is second order in time (24)(25)(26)(27)(28)(29), making accelerations the natural quantity to describe cell motility. Specifically, we previously showed that the migration dynamics of single cells in confinement can be described by the average acceleration as a function of cell position x and velocity v = dx /dt, given by the conditional aver- .…”
Section: Mcf10a and Mda-mb-231 Cells Exhibit Distinct Collision Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Contact Acceleration Maps Reveal Dynamics of Cell-Cell Interactions Here, we aim to describe the underlying interaction dynamics that capture the full stochastic long-timescale behavior of repeatedly colliding cell pairs. The dynamics of single migrating cells are well described by an equation of motion that is second order in time (24)(25)(26)(27)(28)(29), making accelerations the natural quantity to describe cell motility. Specifically, we previously showed that the migration dynamics of single cells in confinement can be described by the average acceleration as a function of cell position x and velocity v = dx /dt, given by the conditional aver- .…”
Section: Mcf10a and Mda-mb-231 Cells Exhibit Distinct Collision Behaviormentioning
confidence: 99%
“…, wherev = dv /dt(27)(28)(29). To uncover the general structure of the cell-cell interactions in our experiments, we therefore first focus on the observed cellular accelerations upon contact as a function of the distance and relative velocity of the cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, cell micropatterning has been utilized to examine dynamic cancer cell processes including migration. A two-state micropatterning with two large rectangular regions connected by a narrow bridge was developed to determine the heterogeneity in migration for established cancer cell lines (Brückner et al, 2020). The migration of MDA-MB-231 cells seeded on one side of the pattern and crossing the small bridge to the second region was recorded and assessed with statistical analysis to reveal potential subpopulations with distinct mechanical and migration capabilities.…”
Section: Substrate Surface Patternsmentioning
confidence: 99%
“…When observing freely migrating cells (i.e., not guided by an external gradient of any kind), one is often struck by the large variation in their migration patterns [1][2][3][4][5], both for a single cell over time, and for a (seemingly identical) cell population. The origin of the large cell-to-cell variability (CCV), or phenotypic, population heterogeneity, observed during cell migration is not understood [6], and is usually ascribed to the inherent noise of cellular systems [7,8].…”
Section: Introductionmentioning
confidence: 99%